Effect of simple and complex carbon sources, low temperature culture and complex carbon feeding policies on poly-3-hydroxybutyric acid (PHB) content and molecular weight (Mw) from Azotobacter chroococcum 6B - Quagliano, J. C. (2001)
The molecular weight (Mw) of poly-3-hydroxybutyrate (PHB), produced by shake-flask culture of Azotobacter chroococcum showed little variation with increasing glucose concentration as carbon source (being in the range of 400–500 kDa), while M; w increased from 300–400 to 640 kDa when grown with increasing concentration of sugar cane molasses. Molecular weight increased nearly 30% from 48 to 72 h culture time when 5% molasses as carbon source was used, while with glucose the highest M; w was reached at 48 h. Under fermentor cultivation A. chroococcum produced PHB with a relatively high M; w of 1590 kDa at 53 h culture time when grown in modified Burk's medium with glucose as carbon source at an initial C/N ratio (molar basis) of 69 under fermentor cultivation. A batch glucose-grown ammonium-limited fermentor culture was repeatedly fed with sugar cane molasses (initial C/N ratio 69) and it was observed that PHB content curve decreased at a slower rate than in the fed-batch culture in which glucose and sucrose were not consumed in the culture medium after the feed.